EFEKTIVITAS PENERAPAN QANUN JINAYAH ACEH: TINJAUAN SISTEMATIS LITERATUR - Zul Azimi (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2026)
This research examines the effectiveness of implementing Jinayat Qanun Number 6 of 2014 in Aceh through a systematic review of 20 scholarly journal articles. The introduction outlines the background of Aceh's special autonomy and the controversy surrounding jinayat law implementation. The research method employs Systematic Literature Review (SLR) with stages of planning, searching, selection, extraction, and thematic synthesis. Analysis results reveal an effectiveness paradox: Jinayat Qanun is symbolically-normatively effective as a strengthener of Islamic identity, yet instrumentally-empirically ineffective in suppressing sharia violation rates (jarimah), which have increased in several regions. This ineffectiveness stems from converging multidimensional factors: weak institutional capacity (human resources, budget, facilities), strong community preference for customary law, and suboptimal socialization. Evaluation from justice and human rights perspectives shows ambivalence, reflecting tension between criticism of discriminatory practices and acknowledgment of efforts to accommodate universal values. The study concludes by recommending a holistic approach through institutional revitalization, harmonization with customary law, participatory socialization, and regulatory refinement to ensure substantive justice.